2016
DOI: 10.3847/0004-637x/821/1/60
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Investigation on the Slowing Down of Cosmic Acceleration

Abstract: Shafieloo ea al. firstly proposed the possibility that the current cosmic acceleration (CA) is slowing down. However, this is rather counterintuitive because a slowing down CA cannot be accommodated in most mainstream cosmological models. In this work, by exploring the evolutionary trajectories of dark energy equation of state w(z) and deceleration parameter q(z), we present a comprehensive investigation on the slowing down of CA from both the theoretical and the observational sides. For the theoretical side, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 96 publications
4
29
0
Order By: Relevance
“…However, some recent work has tried to find a slowing down of the acceleration. Moreover, this novel phenomenon has attracted much attention [48][49][50][51][52][53], including the recent work of [54]. Using the dark energy parameterizations, one found that the cosmic acceleration may already have peaked, and the expansion may be slowing down from the deceleration parameter being q 0 > 0.…”
Section: Convergence Issue In Current Datamentioning
confidence: 99%
“…However, some recent work has tried to find a slowing down of the acceleration. Moreover, this novel phenomenon has attracted much attention [48][49][50][51][52][53], including the recent work of [54]. Using the dark energy parameterizations, one found that the cosmic acceleration may already have peaked, and the expansion may be slowing down from the deceleration parameter being q 0 > 0.…”
Section: Convergence Issue In Current Datamentioning
confidence: 99%
“…(6) and (7), we can reconstruct the deceleration parameter via OHD and distance measurements, respectively. In Figure 1 [23]. In common picture, q(z) decreases from positive to negative with the decreasing redshift.…”
Section: Cosmic Kinematicsmentioning
confidence: 55%
“…Although many parameterizations [23] were considered, there still exists some tensions because of the drive of model-dependence. On the one hand, they were busy balancing the tension between different models.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…For examples, the best FA recipe obtained in this work can be used to constrain various DE models [66][67][68][69][70][71][72][73][74]. Besides, it can be used to explore the dynamical evolution of DE EoS by using various model-independent methods [75][76][77][78][79][80][81][82]. In addition, based on the improved FA technique, a series of related topics, such as dark sector interaction [83], massive neutrino [84], cosmic age [85][86][87], cosmic fate [88] and so on, need to be revisited.…”
Section: Conclusion and Discussionmentioning
confidence: 99%